Interfacial engineering of layered double hydroxide toward epoxy resin with improved fire safety and mechanical property. (1st November 2018) - Li, Zhi; Liu, Zhiqi; Dufosse, François; Yan, Luke; Wang, De-Yi
Abstract: Aiming to imparting epoxy resin (EP) matrix with highly efficient fire safety and mechanical strength, the organically intercalated layered double hydroxide nanosheets (LDH-DBS) were functionalized by silica via electrostatic assembly. EP nanocomposite with resultant nanohybrid LDH-DBS@silica-1 was constructed and verified. Results showed that 3wt% LDH-DBS@silica-1 endowed EP matrix with self-extinguishment (close to V-1) in contrast to burning-to-clamp of EP/3LDH-DBS (EP with 3wt% LDH-DBS). Meanwhile, EP/3LDH-DBS@silica-1 (EP with 3wt% LDH-DBS@silica-1) possessed 63.3% and 29.2% lower peak heat release rate than EP and EP/3LDH-DBS separately, accompanied by remarkably reduced smoke and CO production. The mechanism study illustrated that the optimization of intumescent char accounted for improved fire safety due to the interfacial charring reaction toward stable cordierite (5SiO2 ·2Al2 O3 ·2MgO) and smaller microcrystalline carbon. The spatially preferential assembly of silica on LDH nanosheets was proposed to contribute to the dynamic char reconstruction. In parallel, LDH-DBS@silica-1 enhanced glass transition temperature of EP by 8 °C. The more silica endowed EP matrix with progressively increased non-notched impact strength. In perspective, the interfacial engineering of LDH nanosheets offered an effective approach to strengthening fire safety of polymers. Graphical abstract: Image 1 Highlights: Layered double hydroxide (LDH) was engineered by silica via electrostatic induction. The targeted LDH-DBS@silica-1 formed intercalation structure in epoxy resin matrix. Fire safety was remarkably improved with 3wt% LDH-DBS@silica-1 to EP matrix. Glass transition temperature was increased after silica engineering on LDH-DBS. Impact strength was enhanced with silica engineering due to more craze initiation.